2020
DOI: 10.20944/preprints202005.0420.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Biodentine Versus MTA in Repair of Experimental Furcation Perforation

Abstract: This study compared the Biodentine (BD) and MTA in repair of furcation perforation (FP) in a dog model in terms of inflammatory cell count and new hard tissue formation through histological and immunohistochemical evaluations. Ninety six teeth in six adult mongrel dogs were divided according to the time of repair into two groups (48 teeth/3 dogs each); immediate and delayed repair of the induced FP. Each group was divided into three subgroups (16 teeth each) according to the evaluation periods; 1, 2, and 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To enable adequate healing of exposed dental pulp, the pulp capping material must be bioactive, biocompatible, and antimicrobially active against a variety of microorganisms. 1,4,9 Different pulp capping materials have been studied in the literature, including calcium hydroxide, mineral trioxide aggregate, and other calcium silicate-based compounds. 1,4,10,11 Various studies have shown that calcium hydroxide improves healing and reparative dentin production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To enable adequate healing of exposed dental pulp, the pulp capping material must be bioactive, biocompatible, and antimicrobially active against a variety of microorganisms. 1,4,9 Different pulp capping materials have been studied in the literature, including calcium hydroxide, mineral trioxide aggregate, and other calcium silicate-based compounds. 1,4,10,11 Various studies have shown that calcium hydroxide improves healing and reparative dentin production.…”
Section: Introductionmentioning
confidence: 99%
“…12 Other research recommended using mineral trioxide aggregate (MTA) because it has a superior sealing ability and improves dentinal bridge quality. 9,11,14 MTA disadvantages, such as lengthy setting time and probable discoloration, prompted the development of additional calcium silicatebased polymers, such as biodentine, to address these shortcomings and increase physiochemical qualities. 7,8,14 Tideglusib is a glycogen synthase kinase-3 (GSK-3) inhibitor that belongs to the thiadiazolidine family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation